Reaching Out - Gomez, Catherine (Stimulus: A Medical Humanities Journal, 2023)
An integral part of working in the medical field is being able to connect with people from all walks of life, especially in their most vulnerable moments. The concept for my piece is that a physician is reaching out to a patient who is dejected. I chose to draw the patient upside down to represent their world being “turned upside down” in some way, which is a feeling that many patients describe when battling a chronic illness, whether mental or physical. Even if the physician is not coming from the exact same place as their patient, they still reach out to meet them where they’re at. This is a visualization of how empathy and compassion can pierce through the darkness of isolation. In my piece, I used different colored pens and gouache paint. With black ink, I used pointillism to create a shadow around the patient.